Social work a critical approach to practice - Fook, Jan (SAGE, 2023)
Now 20 years since its first publication, Jan Fook returns to update her seminal text. Celebrating the ageless ideals of the profession, this book throws a life belt to all social work students and professionals looking to engage with the critical tradition of social work to improve their understanding and practice.Part One: Critical Potential and Current Challenges sets the historical and current contexts for critical social work, introducing you to what critical social work is and what it means for practice.Part Two: Rethinking Ideas unpicks the major concepts associated with critical social work, including knowledge, power, discourse, identity, and difference, and how these need to be rethought in new contexts.Part Three: Redeveloping Practices illustrates how these new ideas can inform new practices, proving you with all the tools you need to deliver flexible, responsible and responsive social work practice." --